Belajar Matematika Dengan Menyenangkan Bersama Panti Asuhan Yayasan Nazar Indonesia - Nadira Amalia Nasution; Fajar Utama Ritonga (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Mathematics lessons are very important at the present time, mathematics as a field of study taught in formal educational institutions is an important part of efforts to improve the quality of education. Mathematics lesson is a lesson that deals with many concepts. The problems faced by children in orphanages are generally related to learning, especially mathematics. This happened at the Nazar Indonesia orphanage. The solution offered in this Practicum activity is to utilize YouTube media in the form of animated videos learning mathematics which aims to increase the curiosity of orphanage children in learning Mathematics. This practicum uses the Group Work method proposed by Zastrow, as follows: Intake and contract, Assessment, Planning, Intervention, Evaluation, Termination. The results of this practicum activity are intended so that children in the Nazar Indonesia Orphanage can understand learning in formal educational institutions, especially mathematics.